Irish agriculture and associated industries 1964 - effects of various cereal policies - Henry, Ew; Oconnor, R (Economic & Social Studies, 1970)
In the 1964 structure of Irish Agriculture and associated industries, as published in Paper Number 44 of the Economic and Social Research Institute, the exercises described below investigate the effects on the economy of changes in the 1964 pattern of home-grown cereals: (a) the effects on the economy of substituting home-grown grains for some imported grains, (b) The effects of the converse situation, where most of the required grains are imported.
Keywords: Economics; Sociology